Validation of analytical methodology for quantification of cefazolin sodium by liquid chromatography - Pedroso, Tahisa Marcela [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (FapUNIFESP (SciELO), 2014)
A reversed-phase high performance liquid chromatography method was validated for the determination of cefazolin sodium in lyophilized powder for solution for injection to be applied for quality control in pharmaceutical industry. The liquid chromatography method was conducted on a Zorbax Eclipse Plus C18 column (250 x 4.6 mm, 5 μm), maintained at room temperature. The mobile phase consisted of purified water: acetonitrile (60: 40 v/v), adjusted to pH 8 with triethylamine. The flow rate was of 0.5 mL min-1 and effluents were monitored at 270 nm. The retention time for cefazolin sodium was 3.6 min. The method proved to be linear (r2 =0.9999) over the concentration range of 30-80 µg mL-1. The selectivity of the method was proven through degradation studies. The method demonstrated satisfactory results for precision, accuracy, limits of detection and quantitation. The robustness of this method was evaluated using the Plackett–Burman fractional factorial experimental design with a matrix of 15 experiments and the statistical treatment proposed by Youden and Steiner. Finally, the proposed method could be also an advantageous option for the analysis of cefazolin sodium, contributing to improve the quality control and to assure the therapeutic efficacy

Um método cromatográfico em fase reversa foi validado para a determinação de cefazolina sódica em pó liofilizado, a ser aplicado no controle de qualidade em indústrias farmacêuticas. O método por cromatografia líquida foi conduzido em coluna Zorbax Eclipse Plus C18 (250 × 4,6 mm, 5 µm) mantida à temperatura ambiente. A fase móvel consistiu de água purificada: acetonitrila (60 : 40 v/v), com o pH ajustado para 8 com trietilamina. A vazão usada foi de 0,5 mL min-1 e os analitos de interesse foram monitorizados a 270 nm. O tempo de retenção da cefazolina sódica foi de 3,6 min. As áreas dos picos de cefazolina sódica foram lineares na faixa de concentração de 30-80 µg mL-1 (r2 = 0,9999). A seletividade do método foi demonstrada através de estudos de degradação. O método demonstrou resultados satisfatórios para precisão, exatidão, limites de detecção e de quantificação. A robustez do método foi avaliada utilizando o esquema fatorial de Plackett-Burman com uma matriz de 15 experimentos simultâneos, e analisados por tratamento estatístico proposto por Youden e Steiner. Finalmente, o método proposto pode ser também uma opção de êxito para a análise de cefazolina sódica, contribuindo para o controle de qualidade e para garantir a eficácia terapêutica.
Keywords: Cefazolin sodium/determination; High performance liquid chromatography/reverse-phase/ quantitative analysis; Pharmaceutical industry/quality control; Cefalosporine/quality control; Medicines/ quality control; Cefazolina sódica/determinação; Cromatografia líquida de alta eficiência/fase reversa/ análise quantitativa; Indústria farmacêutica/controle de qualidade; Cefalosporina/controle de qualidade; Medicamentos/controle de qualidade